2021
DOI: 10.1039/d0gc03188g
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed synthesis of 4-cyclohexylmorpholines from reductive coupling of aryl ethers and lignin model compounds with morpholines

Abstract: 4-Cyclohexylmorpholines could be efficiently synthesized from reductive coupling of aryl ethers (including the typical lignin model compounds) with morpholines over Pd/C without using any acidic additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Different Pd-based catalysts also have differences in catalytic performance. Li et al , 49,52–57 Beller et al , 58 Han et al , 59,60 Taddei et al , 61 and He et al 62 demonstrated that Pd-based catalysts exhibited excellent catalytic ability in the process of aminating phenols and ethers. Pd-Based catalysts promote the hydrogenolysis of the C(Ar)–O bonds of ethers and the reduction of phenols to CHONE by the HPd II H species generated by the reaction of Pd-based catalysts and hydrogen donors.…”
Section: One-pot Catalytic Amination Of Lignin Model Compounds Into Chamentioning
confidence: 99%
“…Different Pd-based catalysts also have differences in catalytic performance. Li et al , 49,52–57 Beller et al , 58 Han et al , 59,60 Taddei et al , 61 and He et al 62 demonstrated that Pd-based catalysts exhibited excellent catalytic ability in the process of aminating phenols and ethers. Pd-Based catalysts promote the hydrogenolysis of the C(Ar)–O bonds of ethers and the reduction of phenols to CHONE by the HPd II H species generated by the reaction of Pd-based catalysts and hydrogen donors.…”
Section: One-pot Catalytic Amination Of Lignin Model Compounds Into Chamentioning
confidence: 99%
“…The latter transformation fits the quest for sustainable catalytic methodologies to introduce nitrogen in biomass-derived chemicals. 37–49 To illustrate the robustness of this method, we also show that 10.7 wt% 14CHDO (based on a DO fraction basis) can be derived from a real RCF oligomeric lignin fraction.…”
Section: Introductionmentioning
confidence: 98%
“…On the whole, for the conversion of β‐O‐4 dimers (the major segments in lignin), recent developed strategies overwhelmingly require two or more steps and the presence of transition metal catalysts to harvest N‐containing aromatic compounds. In the limited progresses on the direct conversion of lignin model dimers, Han and co‐workers described Pd‐catalyzed coupling of aryl ethers and morpholines to produce 4‐cyclohexylmorpholines, [8c] Jiao and co‐workers reported a site‐directed C−C bond primary amination of different lignin β‐O‐4 and β‐1 dimers for efficient preparation of anilines, [8d] and Zhang and co‐workers developed CeCl 3 ‐promoted photocatalytic cleavage and amination of lignin β‐O‐4 model compounds to generate N‐containing products [11] . We also reported the direct conversion of lignin β‐O‐4 dimers into benzylamines in the presence of organic amines over Pd/C [12] .…”
Section: Introductionmentioning
confidence: 99%